Value-chain configuration and socio-economic performance into fruit networks: an outlook on long-run insights - Moreno Miranda, Carlos Santiago; Pilamala-Rosales, Araceli Alexandra; Ortiz, Jacqueline; Moreno Miranda, Raúl; Molina-Sánchez, José Isaac; Cerda-Mejía, Liliana; Rama, Daniele (Ediciones INTA, 2019)
The diversification of agri-food products through emerging chains has a fundamental economic role in Ecuador. Socio-economic and productive factors are still affecting their progress and performance. Also, the current growth of market opportunities at the local and international level is a driver to support them. Therefore, this study aimed to analyze social and production aspects to understand the dynamic across the Peruvian groundcherry (Physalis peruviana) chain stages. The goal was to introduce the chain dimensioning to contribute with relevant insights. We performed the research applying a framework that accounts with chain configuration and descriptive tools. The boundaries clustered pre-production, production and post-production actors. We executed surveys at the supply chain levels to identify strengths and weaknesses based on specific socio-economic and productive variables. The paper points out that diversification of marketing channels and the strengthening of organizational structures are the main long-term strategies to reinforce the Peruvian groundcherry chain. The main contribution is the application of the chain configuration as a tool to assess food chain performance comprehensively.